Improve the accuracy and time complexity of code smell detection using SVM and Decision-Tree with Multi-Label Classification - Kaur, Manpreet; Kaur, Deepinder (International Journal of Computer Sciences and Engineering, 2020)
Code smell refers to an anomaly in the source code that shows violation of basic design principles such as abstraction, hierarchy, encapsulation, modularity. In this research we are using SVM (support vector Machine) and decision Tree for code smell detection. In this research we improving the accuracy and time complexity of error in code with the help of Multi-Label classification.